Implementation of Livestock Waste Shredding Machine Technology to Increase the Economic Potential of Goat Breeders in the Muhammadiyah Kartasura Environment - Mangifera, Liana; Wijayanto, Kusuma; Kurniawan, Muhammad Randhy; Faishal, Afif; Abbas, Novel Idris; Jumadi, Jowasrian; Listy, Sheila Rizqya (Universitas Muhammadiyah Surakarta, 2025)
The Kartasura Branch of the Muhammadiyah Economic Council is a division under the auspices of the Kartasura Muhammadiyah Branch Leadership. The Economic Council has several business units, one of which is a goat farming group called Syamsun Farm. Syamsun Farm is a livestock group focused on breeding, buying and selling goats, and processing and selling animal manure. Despite all of Syamsun Farm's potential, it faces challenges such as the ineffective and inefficient processing of organic waste (grass), and the continued use of conventional marketing methods. For example, selling animal manure in sacks, delivering it directly to plant vendors, and offering goats to mosques during Eid al-Adha. Based on these challenges, the P2AD team proposed solutions, including implementing technology using a manure shredding machine and enhancing digital marketing for Syamsun Farm. The outputs of this activity include a manureshredding machine, a module for using and processing animal manure using the shredding machine, the creation of Google My Business, social media platforms, and a marketplace for Syamsun Farm. In addition, video documentation of activities, publications on YouTube and mass media, and nationally accredited journals were also produced.